Nocturnal urine 6-hydroxy sulfate melatonin is associated with the outcome of subjects with sepsis - Wenjie Li; Jiameng Chen; Shuming Pan; Chengjin Gao (Emergency and Critical Care Medicine)
Abstract. Background. It is imperative to identify potential biomarkers for early diagnosis and intervention of severe sepsis. This study investigated the relationship between melatonin secretion and outcome of sepsis after 28-day admission. Methods. Patients with sepsis were randomly divided into an eye mask group and a control group. Blood and urine samples were collected from day 0 to 4. Relevant clinical data and 28-day survival data were obtained. Serum melatonin and urine 6-hydroxy sulfate melatonin (6-SMT) levels were measured. Results. The outcome of sepsis did not differ between the eye mask and control groups. Acute Physiology and Chronic Health Evaluation (APACHE) II and Sequential Organ Failure Assessment (SOFA) scores were significantly higher and monocyte human leukocyte antigen-DR (mHLA-DR), serum melatonin, nocturnal urine 6-SMT, and 24-hour urine 6-SMT levels were significantly lower in the nonsurvivors than in the survivors. The outcome at day 28 after admission was significantly associated with APACHE II and SOFA scores and mHLA-DR, nocturnal urine 6-SMT, and 24-hour urine 6-SMT levels. The areas under the receiver operating characteristic curve were 0.785, 0.740, 0.774, and 0.858 for APACHE II score, SOFA score, mHLA-DR expression, and nocturnal urine 6-SMT amount, respectively. The optimal thresholds for mHLA-DR and nocturnal urine 6-SMT were 30.13% and 43.60%, respectively. Nocturnal urine 6-SMT level was significantly and positively correlated with mHLA-DR expression. Conclusion. Nocturnal urine 6-SMT level may be a feasible biomarker to predict the outcome of patients with sepsis. The use of a night-time eye mask has no significant effect on the outcome of sepsis. Clinical trials. This study was registered at clinicaltrials.gov (NCT02304224).